RANCANG BANGUN APLIKASI STEGANOGRAPHY METODE MINIMUM ERROR LEAST SIGNIFICANT BIT REPLACEMENT (MELSBR) - Aprilia, I; Ariyanti, D; Izzuddin, A (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2018)
Digital data security today is an important part of user because of the increasingly widespread misuse of individuals who can easily open a personal thing. In this case, steganography is a technique that discusses the security of digital data information through the technique of hiding data into other data. Many methods are used in steganography techniques in the process of hiding digital data information. But in this study, the author uses the steganography method based on the insertion of files in the form of files, namely in this case * txt file using the Minimum Error Least Significant Bit Replacement (MELSBR) method with a media storage in the form of 24-bit bitmap files and data that can be inserted in the form of files * txt. The nature of the MELSBR method is to adapt to the local characteristics of the storage medium. In the process of image processing testing researchers use PSNR parameters to determine the quality comparison of digital images before and after processing. The results of this study, concealment and insertion using the MELSBR method with PSNR testing has a greater value so that it can be concluded that the image after processing is getting closer to the cover image.